FOOD COMPOSITION AND HALAL AWARENESS AGAINST INTENTION TO BUY FAST FOOD WITH HALAL CERTIFICATE AS AN INTERVENING VARIABLE - Nasfi Nasfi; Sabri Sabri; Hesi Eka Puteri (Jurnal Apresiasi Ekonomi, 2023)
The aim of the research is to analyze the effect of food composition and halal awareness on the intention to buy fast food with halal certificates as an intervening variable, research in the city of Bukittinggi, the research object of the millennial generation who likes to consume fast food. The population of the Millennial generation aged 15-39 years is 57,099. Non-probability sampling technique, purposive sampling method. The sampling method is the Hair et.al method, the research indicators are 11, the sample is set at 110. The data is processed using the Smart PLS Software. The results of the study found that food composition and halal awareness had a positive and significant effect on the millennial generation's purchase intention of fast food. Halal awareness has no positive and significant effect on purchase intention. The results of the study also found that food composition did not have an indirect effect on the intention to buy fast food in the millennial generation with halal certificates as an intervening variable. Halal awareness does not have an indirect effect on the intention to buy fast food in the millennial generation with halal certificates as an intervening variable.